Collaborative Action Inquiry: A Tool for, and Result of, Parent Learning and Leadership - Paige M. Bray; Joan Pedro; Erin M. Kenney; Mary Gannotti (The University of Alabama, 2022)
This parent information project is grounded in the notion of parental involvement as advocacy that benefits children in the community. Supported by a state-level early childhood foundation in a learning partnership with a national, non-partisan research foundation, this project engaged parent leaders from five communities as co-researchers in identifying assets, listening to citizens, capacity building, and knowledge development. University researchers engaged with co-researchers as essential collaborators enacting this participatory action-oriented project in order to gain insights on family involvement and community action contributing to thriving children, birth to age 8. Creation of a deliberation guide was a tangible product of an iterative cycle of inquiry and grassroots, collaborative process to promote change and empowerment. Co-researcher insights and observations, formally captured in an intentional focus group, are presented with equal importance as author voices. The use of face-to-face time and virtual space is addressed. Implications for parent leadership, transformative knowledge production, and educational change are explored.